The Influence of Leadership Style, Work Motivation, and Work Environment on Employee Productivity in Manufacturing Companies - Ifal Putra Wardana; Syahfa Firnandika Al-Hamid; Lisa Harry Sulistiyowati (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze how leadership style, work motivation, and work environment affect the work productivity of employees of PT Hamsina Jaya - MPGG Cirebon. Using quantitative methods, data was collected by distributing questionnaires to 278 respondents. The analysis techniques applied include validity, reliability, classical assumptions, and hypothesis testing to measure the relationship between variables. The study revealed that leadership style has no positive effect on work productivity. In contrast, motivation and work environment have a positive and significant impact on increasing productivity. Simultaneous tests of the three variables together affect employee productivity. This finding confirms that the main factor in improving productivity is more determined by motivation and a supportive work environment, rather than leadership style. Therefore, companies are advised to focus more on strategies to increase motivation and improve work environment conditions so that optimal productivity can be achieved. In addition, it is necessary to evaluate the effectiveness of the applied leadership style in order to increase its contribution related to employee productivity.